Comparison of Two Types of Pit and Fissure Sealants in Reducing the Incidence of Dental Caries Using a Split-Mouth Design - Miguel Ángel Fernández-Barrera; Teresita de Jesús Saucedo-Molina; Rogelio José Scougall-Vilchis; María de Lourdes Márquez-Corona; Carlo Eduardo Medina-Solís; Gerardo Maupomé (University of Zagreb. School of Dental Medicine, 2021)
Objectives: To evaluate the effectiveness of two pit and fissure sealants (PFS) in reducing the incidence of dental caries in schoolchildren. Material and Methods: A randomized split-mouth experimental design was used in a sample of 140 subjects assigned to two groups. The sealants used were Clinpro©3M and BeautiSealant©Shofu placed in first permanent molars (FPMs). Each sealant was compared to molars in the controls to determine effectiveness over a period of 6 months. The study had a 12.9% loss to follow-up. No statistically significant differences (p>0.05) were observed for sex, age, baseline dmft, or type of sealants. Nonparametric tests were used for statistical analysis. Results: Average dmft index at baseline was 4.10±3.16. Lower incidence of caries was observed in FPMs with pit and fissure sealants (p<0.01), regardless of the type used. When sealants remained intact there was a lower caries incidence compared to sealants partially or completely missing - but differences were only significant for FPM 16. Caries incidence was higher for BeautiSealant sealed teeth than for Clinpro's, but only statistically significant in FPMs 16, 36 and 46 (p< 0.05). Caries incidence was higher in those cases with a higher baseline dmft but it only reached statistical significance in FPMs 26 and 36. Relative risks for dental caries were lower in sealed teeth (p<0.01). Conclusions: Pit and fissures sealants are an effective preventive treatment to reduce caries during a 6-month follow-up in schoolchildren 6 to 8 years of age, regardless of the type of sealant used. The sealant brand that showed greater effectiveness in terms of prevention and retention was Clinpro©3M.